2022
DOI: 10.1099/mic.0.001246
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of MenT2 toxin impairs the growth of Mycobacterium tuberculosis in guinea pigs

Abstract: Toxin–antitoxin (TA) systems are abundantly present in the genomes of various bacterial pathogens. TA systems have been implicated in either plasmid maintenance or protection against phage infection, stress adaptation or disease pathogenesis. The genome of Mycobacterium tuberculosis encodes for more than 90 TA systems and 4 of these belong to the type IV subfamily (MenAT family). The toxins and antitoxins belonging to type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 82 publications
1
4
0
Order By: Relevance
“…Here, we report that relative to the parental strain, Δ menT4 Δ T3 strain was attenuated for growth at both acute and chronic stages of infection in guinea pigs. As observed in the case of ∆mazF3∆9∆6 or ∆vapC22 or Δ higB1 or Δ vapBC3 or Δ vapBC4 or Δ vapBC11 or Δ menT2 , the growth defect associated with Δ menT4 Δ T3 strain was more prominent in spleens and during the chronic stage of infection in guinea pigs 21 , 23 , 25 27 , 35 . In agreement with guinea pig data, we observed that the deletion of menT3 and menT4 also impaired the growth of M. tuberculosis in mice tissues.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Here, we report that relative to the parental strain, Δ menT4 Δ T3 strain was attenuated for growth at both acute and chronic stages of infection in guinea pigs. As observed in the case of ∆mazF3∆9∆6 or ∆vapC22 or Δ higB1 or Δ vapBC3 or Δ vapBC4 or Δ vapBC11 or Δ menT2 , the growth defect associated with Δ menT4 Δ T3 strain was more prominent in spleens and during the chronic stage of infection in guinea pigs 21 , 23 , 25 27 , 35 . In agreement with guinea pig data, we observed that the deletion of menT3 and menT4 also impaired the growth of M. tuberculosis in mice tissues.…”
Section: Discussionsupporting
confidence: 53%
“…However, deletions in either relE1 or relE2 or relE3 or vapC28 or vapC21 or darTG did not reduce M. tuberculosis growth in guinea pigs or mice 21 , 24 , 33 , 34 . In addition to type II TA systems, we have recently shown that MenT2 toxin belonging to the MenAT subfamily is also essential for M. tuberculosis pathogenesis in guinea pigs 35 . Previously, high throughput screening assays such as transposon site hybridization (TRASH) and designer array for defined mutant analysis (DeADMAn) have been performed to identify genes necessary for in vivo growth of M. tuberculosis 36 , 37 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…tuberculosis encodes four MenAT TA systems, comprised of a nucleotidyltransferase (NTase) toxin and a cognate antitoxin belonging to one of three different families (Dy et al, 2014;Xu et al, 2023;Cai et al, 2020). Although, in vivo, menAT2 was recently shown to be required for M. tuberculosis pathogenesis in guinea pigs (Gosain et al, 2022), only menAT1 and menAT3 were shown to act as bona fide TA systems in their native host M. tuberculosis (Xu et al, 2023;Cai et al, 2020). The MenA3 antitoxin inhibits MenT3 through phosphorylation of a serine residue in the catalytic site (Yu et al, 2020), whilst MenA1 forms an asymmetric heterotrimeric complex with two MenT1 protomers, suggesting a different mode of inhibition (Xu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%